Evaluation of an Integrated, Multidisciplinary Program to Address Unsafe Use of Opioids Prescribed for Pain. Issue 7 (23rd March 2017) - Becker, William C; Edmond, Sara N; Cervone, Dana J; Manhapra, Ajay; Sellinger, John J; Moore, Brent A; Edens, Ellen L
Abstract: Objectives: Unsafe use of opioids prescribed for pain is a common challenge in primary care. We aimed to describe a novel clinical program designed to address this issue—the Opioid Reassessment Clinic—and evaluate preliminary efficacy. Methods: The Opioid Reassessment Clinic is a multidisciplinary care team staffed by an internist, addiction psychiatrist, advanced practice nurse, and health psychologist designed to perform enhanced assessment and longitudinal treatment of patients with unsafe use of opioids prescribed for pain. We assessed preliminary efficacy of the clinic using a priori–defined metrics at the patient, provider, clinic process, and health system levels. Results: Of referred patients (N = 87), 84% had a history of substance abuse/dependence and 70% had current misuse of prescribed opioids; 22% received a new substance use disorder diagnosis, each of whom engaged in addiction treatment. Among primary care physicians, 48% referred a patient to the clinic. In terms of process metrics, high fidelity to structured clinical assessments was assisted by templated electronic progress notes. Wait time averaged 22.1 days while length of treatment averaged 137 days. Urine drug testing was performed on 91% of patients an average of 6.4 times, while assessing out-of-system opioid receipt occurred universally. Systems-level findings included evidence of institutional support: hiring a nurse case manager to help with care coordination. Conclusions: Results suggest the Opioid Reassessment Clinic was effective in the management of a small group of high-complexity patients. Wide-scale dissemination may require adapted care models.